A Literature Review of Online Identity Reconstruction - Huang, Jiao; Kumar, Sameer; Hu, Chuan (Frontiers in Psychology, 2021)
The tremendous development of the Internet enables people to present themselves freely. Some people may reconstruct their identity on the Internet to build an online identity that is partly or even completely different from their real identity in the offline world. Given that research on online identity reconstruction is fragmented, it is important to evaluate the current state of the literature. In this paper, a review of literature related to online identity reconstruction was conducted. This study summarized the theoretical and methodological preferences of relevant research. In addition, it elaborated why and how people engage in online identity reconstruction. The predictors and effects of online identity reconstruction were also discussed. The results of this study provided an overview of the thematic patterns of existing research. This review also identified current research gaps and recommended possible directions for future studies.